Scientific programming C-language, algorithms and models in science - Barone, Luciano M. (Luciano Maria); Marinari, Enzo; Organtini, Giovanni; Ricci-Tersenghi, F. (Federico) (World Scientific, 2014)
This important book fills a gap in current available bibliography. There are many manuals for programming in C, but they never explain programming technicalities to solve a given problem. This book illustrates many relevant algorithms and shows how to translate them in a working computer program